The Effect Of Mudharabah, Murabahah, And Ijarah Financing On Profitability (Roa) At Islamic Commercial Banks In Indonesia 2015-2017 - Indrawati, Ria (Universitas Islam Negeri Alauddin Makassar, 2021)
ABSTRACT- This study aims to determine the effect of mudharabah, murabahah and ijarah financing on profitability (ROA) at Islamic commercial banks in Indonesia in 2015-2017. Sampling in this study were 13 Islamic commercial banks registered with the Financial Services Authority in the period June 2015-November 2017. Islamic banking also requires good performance supervision by banking regulators. One indicator to assess the financial performance of a bank is to look at the level of profitability. The method used in this study is a quantitative approach with data analysis techniques used, namely classical assumption test, descriptive statistics and hypothesis testing. The results of this study are mudharabah financing has a negative and significant effect on ROA, murabahah financing has a positive and insignificant effect on ROA, ijarah financing has a positive and insignificant effect on ROA, and simultaneously mudharabah, murabahah and ijarah financing have a significant effect. affect. affect the profitability of ROA at the bank. general sharia law in Indonesia in 2015-2017. Keywords: Mudharabah, Murabahah, Ijarah, Profitability (ROA)